2018
DOI: 10.1029/2018jd028402
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Indonesian Fires and Drought With the Type of El Niño and Phase of the Indian Ocean Dipole During 1979–2016

Abstract: This study advances the previous understanding of the role of climate variability on Indonesian fire activity, by considering (i) the presence of different types of El Niño and (ii) the interaction between El Niño and the Indian Ocean Dipole (IOD). We classify 12 El Niño events during 1979-2016 into Eastern Pacific (EP) and Central Pacific (CP) types (four and eight El Niño events, respectively) and analyze observational data of sea surface temperature, precipitation, drought code, biomass burning carbon emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 57 publications
7
81
1
3
Order By: Relevance
“…Partial contribution of the burned area with Niño3.4, α·Niño3:4 in equation (1), follows the seasonal pattern of the Niño3.4-DMI index; however, the maximum for partial contribution with DMI, β · DMI in equation (1), is in October and it is higher than α·Niño3.4 in October and November, possibly because the IOD peaks in October and November. It means that the IOD also has a substantial role in the fire activity together with Niño3.4 as consistent with previous studies (Field et al, 2009;Pan et al, 2018). We found that correlations between burned area and Niño3.4-DMI index are significant for all months.…”
Section: Equatorial Asia Fire Diversitysupporting
confidence: 93%
“…Partial contribution of the burned area with Niño3.4, α·Niño3:4 in equation (1), follows the seasonal pattern of the Niño3.4-DMI index; however, the maximum for partial contribution with DMI, β · DMI in equation (1), is in October and it is higher than α·Niño3.4 in October and November, possibly because the IOD peaks in October and November. It means that the IOD also has a substantial role in the fire activity together with Niño3.4 as consistent with previous studies (Field et al, 2009;Pan et al, 2018). We found that correlations between burned area and Niño3.4-DMI index are significant for all months.…”
Section: Equatorial Asia Fire Diversitysupporting
confidence: 93%
“…The length of the fire seasons in the southern Siberia (virgin boreal forest) has been projected to increase by at least one month due to the lack of precipitation [51,70], drier climate; higher fire danger would likely lead to huge CO emissions from fires. Pan et al [71] found that fires are always more intensive in southern Kalimantan than in southern Sumatra in all EI Niño events in 1979-2016. More intense and prolonged Indonesian drought and fires occur in the Eastern Pacific type, during which the emitted carbon amounts almost double those in the Central Pacific type.…”
Section: Impacts Of Biomass Burning On the Interannual Variation And mentioning
confidence: 99%
“…This ENSO-cycle to CO anomaly relationship is caused by an increase in the Indonesian fire emissions due to the El Niño induced drought, and by a decrease in Indonesian fire emissions due to the La Niña induced high precipitation (e.g., . It is also known that the positive Indian Ocean Dipole (IOD) intensifies the drought-induced Indonesian fires (e.g., Field et al 2009;Pan et al 2018). These studies strongly suggest that some combination of multiple climate components influence the CO IAV observed in the upper troposphere.…”
Section: Link Between Co and Climatementioning
confidence: 99%